(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The historical experience of interaction between Central Asia and external powers provides a deeper understanding of contemporary political processes in the region. In this context, the study of China’s foreign policy strategies, beginning with key stages of its historical development, is of particular importance. One such stage is the Qing dynasty period (1644–1912), during which China achieved significant success in territorial expansion, political consolidation, and foreign policy activity, including in Central Asia. Analyzing the Qing dynasty’s foreign policy in the region allows for an assessment of past diplomatic approaches and reveals the roots of the modern strategies of the PRC, which reflect a strong sense of historical continuity.